Numerical Approximation of Multi-Phase Penrose-Fife Systems - Gräser, Carsten; Kahnt, Max; Kornhuber, Ralf (Computational Methods in Applied Mathematics, 2016)
We consider a non-isothermal multi-phase field model. We subsequently discretize implicitly in time and with linear finite elements. The arising algebraic problem is formulated in two variables where one is the multi-phase field, and the other contains the inverse temperature field. We solve this saddle point problem numerically by a non-smooth Schur-Newton approach using truncated non-smooth Newton multigrid methods. An application in grain growth as occurring in liquid phase crystallization of silicon is considered.
CRIS-Team Scopus Importer:2022-03-23
Keywords: Finite Elements; Multi-Phase Field Models; Parabolic Variational Inequality; Partial Differential Inclusion; Phase Transitions; Thermodynamic Consistency